The Changing Transitions to Adulthood across Southeast Asia: A Census Approach to Cross-National Comparisons. Issue 1 (March 2013) - Nahar, Quamrun; Xenos, Peter; Abalos, Jeofrey
Using data from the national censuses of five Southeast Asian countries, this article examines entropy-based measures of the heterogeneity in a set of five markers of the transition to adulthood. Our results suggest that the transition to adulthood is becoming increasingly complex over time in all five countries; complexity is greatest for females, and important cross-national differences in heterogeneity levels and timing persist when underlying patterns of economic transformation are considered. In light of these persistent cross-national differences, we suggest that our census-based analysis should be complemented with case studies of these countries that focus on cultural or institutional influences. Results related to the importance of schooling suggest that cross-national comparisons of educational institutions would be fruitful.